William Shakespeare's Julius Caesar [videorecording (DVD)] - Mankiewicz, Joseph L.; Brando, Marlon; Mason, James, 1890-1959; Gielgud, John, 1904-2000; Calhern, Louis, 1895-1956; O'Brien, Edmond, 1915-1985; Garson, Greer, 1904-1996; Kerr, Deborah, 1921-2007; Shakespeare, William, 1564-1616 (Distributed by Warner Home Video, 2006)
An adaptation of the classic Shakespeare play, chronicling the events around the assassination of Julius Caesar.